Indirect causes of maternal mortality at Korle Bu Teaching Hospital - Collison, A.H.K.; Peterson, F.C.; Aniteye, P. (Ghana Medical Journal, 2003)
A total of 439 maternal deaths were recorded at the Korle-Bu Teaching Hospital from January 1995 to December 1999.0ne hundred and seventy-one (39%) of these deaths were due to indirect Causes which arc medical conditions complicating pregnancy. Anaemia was the leading medical cause of death and it was responsible for 46 (10.5%) of the deaths. Other important causes of death were sickle cell disease (7 .3%). ren al disease (4.1%) and diabetes mellitus (3.6%). The multidisciplinary approach in the management of medical conditions complicating pregnancy yields optimum results and there is the need to involve physicians in the management of these cases. Joint clinics in which the obstetrician and the physician see such patients will be ideal
Journal Article
Keywords: Maternal mortality; medical conditions in pregnancy; multidisciplinary approach; joint clinics